Bone Marrow-Derived Mesenchymal Stem Cells: Current and Future Applications in the Urinary Bladder - Beth A. Drzewiecki; John C. Thomas; Stacy T. Tanaka (Stem Cells International)
Mesenchymal stem cells can be isolated from almost any adult tissue. In this paper we focus on bone marrow-derived mesenchymal stem cells which have captured the interest of researchers since their introduction because of the promising potential of tissue regeneration and repair. They are known for their ability to self-renew and differentiate into diverse lineages while maintaining low immunogenicity. The exact mechanisms behind how these cells work still remain unclear, and there is a continuing shift in the paradigms that support them. There has been extensive research in multiple organ systems; however, the genitorurinary system has been vastly underrepresented. This article discusses the background behind bone marrow-derived mesenchymal stem cells and they are currently being applied to the urinary bladder in the realm of tissue engineering. We also postulate on their future applications based on the current literature in other organ systems.